Potret Kesejahteraan Masyarakat di Provinsi Nusa Tenggara Timur - Erwin Ndakularak (Universitas Kristen Wira Wacana Sumba, 2014)
Autonomy region is the rights, authority, and obligation of otonomous region to arrange and manage its own governance administration and the interests of local society in accordance to law and regulation. Through autonomy region, local government has right and authority to plan, formulate and excute the policy of development program which is adapted to local needs and requirements. The purpose of this research is to see the picture of society prosperity in East Nusa TenggaraKeyword: Human Development Index and Poverty